PENGARUH TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP PENDIDIKAN INDONESIA - Abu Huraerah, Ahmad Junaedy; Abdullah, Abdurrahman Wahid; Rivai, Alimuddin (Journal of Islamic Education Policy, 2023)
This journal discusses about the influence of Information and Communication Technology (ICT) on education in Indonesia. The use of ICT in education has been evolved and  it is used as a tool to enhance the quality of education and opening access for the public. However, the use of ICT also has both positive and negative impacts that need to be considered. This research indicates that ICT has a significant influence in education, enabling easy and fast access to various types of information from around the world, facilitating communication among individuals, fostering innovation and research ideas, and changing the way we interact with others worldwide. However, the use of ICT also has negative effects such as internet misuse and gadget addiction. To maximize the use of ICT in education, cooperation between the government, schools, and the community is essential. Fast and affordable internet access must be ensured, and an optimal curriculum that incorporates ICT usage needs to be developed. Training on ICT usage in teaching should also be provided to teachers and lecturers, while supervision of ICT usage in the school or campus environment needs to be enhanched. Keywords: Influence, Technology of Information, Education.Top of Form  AbstrakJurnal ini membahas pengaruh Teknologi Informasi dan Komunikasi (TIK) terhadap pendidikan di Indonesia. Penggunaan TIK dalam pendidikan telah berkembang pesat dan digunakan sebagai alat untuk meningkatkan kualitas pendidikan dan memperluas akses bagi masyarakat. Namun, penggunaan TIK juga memiliki dampak positif dan negatif yang perlu dipertimbangkan. Penelitian menunjukkan bahwa TIK memiliki pengaruh signifikan pada pendidikan, memungkinkan akses mudah dan cepat ke berbagai jenis informasi dari seluruh dunia, memfasilitasi komunikasi antar individu, mendorong inovasi dan ide penelitian, dan mengubah cara kita berinteraksi dengan orang lain di seluruh dunia. Namun, penggunaan TIK juga memiliki dampak negatif seperti penyalahgunaan internet dan kecanduan gadget. Untuk memaksimalkan penggunaan TIK dalam pendidikan, diperlukan kerja sama antara pemerintah, sekolah, dan masyarakat. Akses internet yang cepat dan terjangkau harus dijamin, dan kurikulum yang optimal yang mencakup penggunaan TIK perlu dikembangkan. Pelatihan tentang penggunaan TIK dalam pembelajaran juga perlu diberikan kepada guru dan dosen, sementara pengawasan penggunaan TIK dalam lingkungan sekolah atau kampus perlu ditingkatkan.